Pola Komunikasi Keluarga Untuk Mengembangkan Sosial Emosional Anak Usia Dini Di Desa Bungah Gersik - Denisa, Ayu; Amalia, Dwi Risky; Faiqoh, Elok; Umairi, Mushab Al (Journal of Childhood Education, Development and Parenting, 2024)
Social emotional development is a competency that every child must have in order to be able to adapt to their environment, both socially, namely the child is able to interact and communicate with the family, school and community environment, and emotionally, namely the child is able to express and express what he feels within himself. This research aims to describe the role of parents in the social emotional development of children in Bungah village. This research is a qualitative descriptive study with the research subjects being four children's parents. The data collection techniques used were observation, interviews and documentation. Meanwhile, data analysis techniques include data reduction, data presentation, and drawing conclusions. This research uses data validity tests in the form of triangulation and extended observations. The results of the research show that the role of parents in the social emotional development of children is that parents act as educators, parents act as mentors, parents act as supervisors, parents act as facilitators and parents act as friends.